Impact of Nosema ceranae and Nosema apis on individual worker bees of the two host species (Apis cerana and Apis mellifera) and regulation of host immune response - Chainarong Sinpoo (2018)
© 2017 Elsevier Ltd Nosema apis and Nosema ceranae are obligate intracellular microsporidian parasites infecting midgut epithelial cells of host adult honey bees, originally Apis mellifera and Apis cerana respectively. Each microsporidia cross-infects the other host and both microsporidia nowadays have a worldwide distribution. In this study, cross-infection experiments using both N. apis and N. ceranae in both A. mellifera and A. cerana were carried out to compare pathogen proliferation and impact on hosts, including host immune response. Infection by N. ceranae led to higher spore loads than by N. apis in both host species, and there was greater proliferation of microsporidia in A. mellifera compared to A. cerana. Both N. apis and N. ceranae were pathogenic in both host Apis species. N. ceranae induced subtly, though not significantly, higher mortality than N. apis in both host species, yet survival of A. cerana was no different to that of A. mellifera in response to N. apis or N. ceranae. Infections of both host species with N. apis and N. ceranae caused significant up-regulation of AMP genes and cellular mediated immune genes but did not greatly alter apoptosis-related gene expression. In this study, A. cerana enlisted a higher immune response and displayed lower loads of N. apis and N. ceranae spores than A. mellifera, suggesting it may be better able to defend itself against microsporidia infection. We caution against over-interpretation of our results, though, because differences between host and parasite species in survival were insignificant and because size differences between microsporidia species and between host Apis species may alternatively explain the differential proliferation of N. ceranae in A. mellifera.